STUDY OF THE ADDITION OF RED PALM OIL (RPO) TO THE SENSORY AND CHEMICAL CHARACTERISTICS OF BEEF SAUSAGE - Winny Iftari; Riska Amalia; Agustin Nurya Savitri; Gimelliya Saragih (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2022)
Synthetic antioxidants are widely used to inhibit quality deterioration of the beef sausage. This study utilizes the high carotene content in Red Palm Oil (RPO) as a substitute for vegetable oil in beef sausage. This study aims to determine the sensory and chemical characteristics of beef sausage with the addition of RPO 5%, 10%, and 15%, and obtain the best formulation. Based on the study, it is known that beef sausage with the addition of RPO 10% received the highest overall sensory rating with an average score of 5.35 out of 7. The chemical characteristics of beef sausage include water content, protein content, and fat content that have met the standard of SNI 3820:2015. However, the ash content of beef sausage with the addition of RPO exceeds the maximum ash level that has been set by the SNI. The beta carotene level of beef sausage in the 5% RPO formula was 592.44 ppm, in the 10% RPO formula it was 596.89 ppm, and in the 15% RPO formula, it was 603.56 ppm. The 10% RPO formulation produces beef sausages with the best sensory and chemical characteristics.